Paraoxonase 1 gene polymorphısms (Q192r and L55m) and assocıatıon wıth coronary slow flow - Akgün, Arzu Neslihan; Yavuzkır, Mustafa Ferzeyn; Akbulut, Mehmet (My University, 2023)
Aim: Coronary slow flow (CSF) is an angiographic entity characterized by slow progression of opaque material and an early indicator of atherosclerosis. Paraoxonase 1 (PON1) protects high-density lipoprotein (HDL) and low-density lipoprotein (LDL) from oxidative modifications. PON 1 has two amino acid polymorphisms (192Q/R and 55L/M) and that affect its functioning. We aim to determine PON1 two genetic polymorphisms and relationship with CSF. As we know, our study is the first to assessment the relationship PON1 gene polymorphisms (L55M and Q192R) and CSF. Material and Methods: We included a total of 100 patients and 2 groups as normal coronary flow (NCF) and CSF. Genomic sequences of rs854560 and rs662 polymorphisms were determined using polymerase chain reaction. The research protocol was approved by Fırat University Institutional Review Board (Approval No:16). Results: The mean age of CSF group was 45.4±17 and NCF group was 50.5±11 years. There was the statistically difference in terms of the frequency of carrying Q and R alleles. For dual genotypes, the QQLM genotype was more common in CSF group, whereas the QRLM genotype was more common in NCF. Significant differences were found between patients with QQLM, RRLL, RRLM and QRLM genotypes and healthy individuals. Conslusion: We found a significant relationship between the Q allele and the QQLM genotype and CSF, and we thought that these may be risk factors for CSF. In addition, the fact that the R allele and QRLM, RRLL, and RRLM genotypes were higher in the NCF group and there was a statistically significant relationship suggested that these might be protective factors for CSF.
Keywords: Coronary slow flow; paraoxonase; gene polymorphism; antioxidant